Construções de tópico em foco: uma investigação sobre o fenômeno da topicalização na cidade de Governador Nunes Freire/MA - BRANCO, Thaísa Helena Peixoto Castelo (2019)
This dissertation aims to describe and analyze the speech of the city of Governador Nunes Freire as a locus that manifests signs of Brazilian Portuguese, from the phenomenon of the Constructions of Topic, within the scope of the syntax of the Portuguese Language. In our study, we sought to investigate how such phenomenon is presented in the speech of the inhabitants of that city - considering the community of practice of this investigation the participants involved in criminal hearings - to know if this phenomenon interferes in the structural relations that govern our language. To do this, we use the following methodology: sociolinguistic research, of an exploratory qualitauantitative nature, whose process includes data collection, definition of social groups, linguistic description of the data and analysis of the results obtained. The data presented here were collected from testimonials provided at the Governador Nunes Freire / MA municipality forum, between 2015 and 2018, totaling 16 statements, divided into groups of men and women, subdivided by age group and schooling. As a theoretical basis, we use Functionalism as the epistemological basis of Sociolinguistics, as well as its aspects: Interactionist Sociolinguistics and Sociofunctionalism, considering that the fundamental principle of the aforementioned theories is to analyze the language in use, as we propose in this job. The concept of the topic used in our study is that of Perini (2006), which classifies it as a discursive function, which, although it is represented formally (placement at the beginning of the period), has to do with the communication situation, concept that best fits within the scope of our research. Thus, we work with the ideas of Sentential Topic and Discursive Topic, verifying which of the two types is more frequent in each group and if social factors influence in these realizations, being verified that the achievements of the Topic Constructions are present in all the groups of speakers investigated, regardless of gender. However, we noticed that the age group factor and the schooling factor were predominant in different social segments, with the Sentential Topic being more frequent in a group of younger age groups and the most frequent Discourse Topic in the group of men with higher schooling. We also perceive in the speech of that community of practice that, although it can not always be analyzed syntactically, the topic does not agramaticalize the syntax of the prayers of our language, on the contrary, it makes communication more dynamic and fluid. Since, more than a syntactic function, the topic has a communicative function, and should not therefore be analyzed in a decontextualized way.